Taxonomy, Genomics and Ecophysiology of Hydrocarbon-Degrading Microbes 2017
DOI: 10.1007/978-3-319-60053-6_9-1
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Hydrocarbon-Degrading Alphaproteobacteria: Sphingomonadales

Abstract: The bacterial order Sphingomonadales includes many Sphingomonadaceae and Erythrobacteraceae isolates that have the ability to degrade a wide range of hydrocarbons. Hydrocarbon-degrading members of the Sphingomonadaceae (mainly belonging to the genera Sphingomonas, Sphingobium, Novosphingobium, and Sphingopyxis) are common Gram-negative aerobic organisms that have been isolated from a wide variety of environments, including

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 132 publications
0
9
0
Order By: Relevance
“…Within each of the lifestyle categories the taxonomic assignation of the ASVs was phylogenetically diverse (Figure 1b), but there were notable differences in how these ASVs contributed to each category in the rDNA and the RNA pool. FL-ls assemblages in the rDNA were largely represented by sequences of the putatively chemolithotrophic Crenarchaeota [48] and SAR324 [14], and by Chloroflexi (mostly SAR202), Marinimicrobia and the Alphaproteobacteria Sphingomonadales, which may have the ability to use recalcitrant compounds [15, 49, 50]. In contrast, in the rRNA pool, Sphingomonadales took over and accounted for half of the reads (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…Within each of the lifestyle categories the taxonomic assignation of the ASVs was phylogenetically diverse (Figure 1b), but there were notable differences in how these ASVs contributed to each category in the rDNA and the RNA pool. FL-ls assemblages in the rDNA were largely represented by sequences of the putatively chemolithotrophic Crenarchaeota [48] and SAR324 [14], and by Chloroflexi (mostly SAR202), Marinimicrobia and the Alphaproteobacteria Sphingomonadales, which may have the ability to use recalcitrant compounds [15, 49, 50]. In contrast, in the rRNA pool, Sphingomonadales took over and accounted for half of the reads (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…The Order Rickettsiales is represented by the genus Rickettsia , which is a symbiont of Eukaryota and can induce disease in humans [ 85 ]. Sphingomonadales ( Sphingomonas , Novosphingobium , Sphingobium , Sphingopyxis and Erythrobacter ) are common aerobic bacteria isolated from a wide range of environments, including temperate and polar soils, marine sediments and plant surfaces and tissues [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…The relative abundance of Sphingomonas was less than 1% in 1-year and more than 1.4% in 14-year treatments, showing an increase with CC. Other studies have shown that Sphingomonas was a nutrient-poor nanobacterium, which could adapt to heterotrophic growth under conditions of nutrient depletion ( Kämpfer et al, 2002 ; Delmotte et al, 2009 ; Williams et al, 2009 ; Sharma et al, 2010 ; Kertesz et al, 2017 ). In this paper, the increase of Sphingomonas indicates that after 14 years of continuous cultivation, the rhizosphere soil presented a state of nutrient depletion.…”
Section: Discussionmentioning
confidence: 99%